Integrated Proteomics and Transcriptomics Analyses Reveal the Transcriptional Slippage of a Bymovirus P3N-PIPO Gene Expressed from a PVX Vector in Nicotiana benthamiana - Chulang Yu; Runpu Miao; Zhuangxin Ye; Stuart MacFarlane; Yuwen Lu; Junmin Li; Jian Yang; Fei Yan; Liangying Dai; Jianping Chen (Viruses, 2021)
P3N-PIPO (P3 N-terminal fused with Pretty Interesting Potyviridae ORF), the movement protein of potyviruses, is expressed as a translational fusion with the N-terminus of P3 in potyviruses. As reported in previous studies, P3N-PIPO is expressed via transcriptional slippage at a conserved G2A6 slippery site in the genus Potyvirus. However, it is still unknown whether a similar expression mechanism of P3N-PIPO is used in the other genera of the family Potyviridae. Moreover, due to the extremely low expression level of P3N-PIPO in natural virus-infected plants, the peptides spanning the slippery site which provide direct evidence of the slippage at the protein level, have not been identified yet. In this study, a potato virus X (PVX)-based expression vector was utilized to investigate the expression mechanism of P3N-PIPO. A high expression level of the P3N-PIPO(WT) of turnip mosaic virus (TuMV, genus Potyvirus) was observed based on the PVX expression vector. For the first time, we successfully identified the peptides of P3N-PIPO spanning the slippery site by mass spectrometry. Likewise, the P3N-PIPO(WT) of wheat yellow mosaic virus (WYMV, genus Bymovirus) was also successfully expressed using the PVX expression vector. Integrated proteome and transcriptome analyses revealed that WYMV P3N-PIPO was expressed at the conserved G2A6 site through transcriptional slippage. Moreover, as revealed by mutagenesis analysis, Hexa-adenosine of the G2A6 site was important for the frameshift expression of P3N-PIPO in WYMV. According to our results, the PVX-based expression vector might be used as an excellent tool to study the expression mechanism of P3N-PIPO in Potyviridae. To the best of our knowledge, this is the first experimental evidence dissecting the expression mechanism of a bymovirus P3N-PIPO in the experimental host Nicotiana benthamiana.